Kepatuhan Antenatal Care Dengan Kejadian Preeklampsia Pada Ibu Hamil Di Puskesmas Kayon Kota Palangkaraya - Fitriani Ningsih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The maternal mortality rate (MMR) is one indicator to look at the degree of women's health. Death of women of childbearing age is caused by problems related to pregnancy, childbirth, and the puerperal, one of which is a result of preeclampsia. The purpose of this study was to analyze the relationship between antenatal care adherence with the incidence of preeclampsia in pregnant women at the Kayon Health Center in Palangka Raya City. The design of this study is analytical research with a retrospective approach. The study population was pregnant women recorded in the 2018 medical records and the sample size of this study was 150 respondents with a sampling technique used was consecutive sampling. The statistical test used in this study is chi-square. The results of statistical tests can be concluded that there is a relationship between antenatal care compliance with preeclampsia with a Value P-value of 0.001. Therefore, it is necessary to promote health about the importance of carrying out regular antenatal care visits so that health workers can make early detection of symptoms of preeclampsia in the mother.